Endophytic Fungi Isolated from Plants Present in a Mine Tailing Facility Show a Differential Growth Response to Lead - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Ortiz-Calderon, C; Parada-Fuentes, R (WILEY, 2022)
Plants growing in metal-polluted sites can be a source of micro-organisms suitable for bio-assisted phytoremediation strategies. In this work, three endophytic fungi from the roots of Poa stuckertii and Poa pratensis, two grasses that naturally colonize a Lead-Zinc tailing storage facility in Southern Chile, were isolated and identified. The leachate of the tailing sands showed a Pb content of 1 center dot 36 +/- 0 center dot 71 ppm, and a pH of 7 center dot 3. By amplifying the ITS1/ITS4 region of fungal ribosomal DNA, the isolates were identified as Bjerkandera sp., Microdochium sp. and Sarocladium sp. When the growth media was supplemented with 50 ppm of Pb at pH 4 center dot 5, Microdochium sp. showed an 80% decrease in the biomass, but the biomass production of Bjerkandera sp. and Sarocladium sp. was not affected by the same treatment. The accumulation of Pb in Microdochium sp. increased as a function of the concentration of the metal in the growth media, between 48 center dot 3 and 241 center dot 3 mu mol l(-1). We showed that two Poaceae plants growing on a Lead-Zinc tailing storage facility are a source of endophyte fungi and that Pb had a differential effect on the growth of the isolated fungi independent of the plant of origin.